Effect of Homoeopathic Medicine Cephalandra Indica on Glucose Metabolism, β cell Function and Insulin Resistance in Adults of Type 2 Diabetes: Double Blind, Placebo Controlled Cross Over Study (Advancements in Homeopathic Research, 2022)
Background: To assess the efficacy of homoeopathic medicine Cephalandra indica on glucose metabolism, b cell function and insulin resistance in adults of type 2 diabetes. Methods: 100 patients were enrolled in the study and categorized into 2 groups, group I and group II. After one month of stabilization period Group I were given Homoeopathic medicine Cephalandra Indica and Group II with Placebo; followed by one month washout period. Afterwards regimen was interchanged for 6 months. Biochemical and anthropometric data was recorded at baseline, at 3rd month and at 6th month, after stabilization, before and after washout and at the end of study. Results: An improving trend was observed in both the groups for Cephalandra Indica Q (FBS 176.32±17.08 to 130.82±3.55 mg/dl p< 0.05 in group I and FBS 185.60±27.61 to 140.28±10.37 in group II). HbA1C improved due to Cephalandra Indica in group I (7.96±1.08 to7.40±.65) & in group II (8.23±1.07 to 6.77±.54). The HOMA IR reduced from 8.92±2.20 to 5.78±1.44 in group I as well as 11.44±5.03 to 6.88 in group II & HOMA Beta cell function improved from 66.03±16.62 to 95.10±23.69 in group I and 77.36±43.19 to 93.43±33.75 in group II. Conclusion: In freshly diagnosed type-2 diabetics Cephalandra indica reduced FBS, HbA1c, Insulin resistance and also significantly increased the beta cell functioning. It shows hypoglycemic effect of Cephalandra indica.
Keywords: Homoeopathic Medicine; Cephalandra Indica; Glucose Metabolism; β cell Function; Insulin Resistance; Double Blind